Paper-Based Microfluidic Device for Determination of Nitrite in Pickled Vegetables - Xu, Chunxiu; Zhong, Minghua; Wu, Yunying; Cai, Longfei; Hong, Jiani; Huang, Yuna (Asian Journal of Chemistry, 2014)
Nitrite is a carcinogen which has been detected in various foods including pickled vegetables, cured meat and fish products. Development of cost effective, simple and easy-to- use method for determination of nitrite in foods is thus highly desirable, especially for those foods that traditionally contains high contents of nitrite. In this work, a paper-based microfluidic analytical method was proposed for the determination of nitrite in pickled vegetables. Determination of nitrite was based on the chromogenic reaction between nitrite and mixed chromogenic reagents on a paper-based microfluidic device. This method offers advantages of easy fabrication, low reagents/sample consumption, ease of use, fast analysis speed and low cost, which may have potential in food safety testing for household use.